2009
DOI: 10.2478/v10125-009-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

<i>Bythinella hansboetersi</i> Glöer et Pešić, 2006 (Gastropoda: Rissooidea) in Bulgaria: Its Morphology, Molecular Distinctness, and Phylogeography

Abstract: For five populations of Bythinella from Bulgaria the shell, penis, and female reproductive organs are figured and briefly described. 27 sequences of COI (mtDNA), and 14 of ITS-1 (rRNA) are used to infer phylogenetic relationships among the studied populations and five Central European Bythinella species. All five studied populations belong to the same species: B. hansboetersi Glöer et Pešiae, 2006, which is morphologically and molecularly distinct from B. austriaca earlier reported from Bulgaria. NCA analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Recently we found six molecularly distinct species of this genus in Romania (FALNIOWSKI et al 2009a, b) and ten molecularly distinct (9 of them not yet described) species in Greece (FALNIOWSKI & SZAROWSKA 2011). Several nominal species were recently reported from Bulgaria (GLÖER & PEŠIAE 2006, FALNIOWSKI et al 2009a, GLÖER & GEORGIEV 2009) and Montenegro (GLÖER & PEŠIAE 2010). FALNIOWSKI et al (2009b, c) and FALNIOWSKI & SZAROWSKA (2011) demonstrated that (1) the morphostatic mode of evolution as defined by DAVIS (1992) is common in Bythinella; (2) it is impossible to distinguish Bythinella species if there are no molecular data, although the morphology must be considered as well (BICHAIN et al 2007b, HAASE et al 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we found six molecularly distinct species of this genus in Romania (FALNIOWSKI et al 2009a, b) and ten molecularly distinct (9 of them not yet described) species in Greece (FALNIOWSKI & SZAROWSKA 2011). Several nominal species were recently reported from Bulgaria (GLÖER & PEŠIAE 2006, FALNIOWSKI et al 2009a, GLÖER & GEORGIEV 2009) and Montenegro (GLÖER & PEŠIAE 2010). FALNIOWSKI et al (2009b, c) and FALNIOWSKI & SZAROWSKA (2011) demonstrated that (1) the morphostatic mode of evolution as defined by DAVIS (1992) is common in Bythinella; (2) it is impossible to distinguish Bythinella species if there are no molecular data, although the morphology must be considered as well (BICHAIN et al 2007b, HAASE et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In Romania (FALNIOW-SKI et al 2009a, b) we found greater genetic differences between Bythinella species than in Greece (FAL-NIOWSKI & SZAROWSKA 2011). However, the data on the genus inhabiting the zone between Romania and Bulgaria are scarce (FALNIOWSKI et al 2009a). Thus the aim of the present paper was to answer the following questions: (1) Can the pattern of genetic differentiation, decreasing from north to south, be applied to all the Balkans?…”
Section: Introductionmentioning
confidence: 99%
“…The divergence of Bythinella has primarily been studied in western, southern and central Europe (Boeters, 1973(Boeters, , 1998Giusti & Pezzoli, 1977;Falniowski, 1987), but these studies concentrated mostly on external morphology and anatomy, initially of the shell and later, of the soft body parts. However, morphology only cannot be used for the unequivocal delimitation of species because of the limited number of taxonomically useful characters and the high variability of those characters (Falniowski, 1987(Falniowski, , 1992Bichain et al, 2007;Falniowski et al, 2009a). In more recent studies with molecular data, several Bythinella species were identified and also several nominal species were synonymised (Bichain et al, 2007;Haase et al, 2007;Benke et al, 2009;Falniowski et al, 2009aFalniowski et al, , b, 2012bFalniowski & Szarowska, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Truncatelloidea, as already stated, the shell morphology is often not sufficient for reliable species delimitation (e.g. FAlniOwski et al 2009a), and phylogenetic studies require the soft parts of the animals for anatomical studies and DNA extraction.…”
Section: Isolation In Long-lasting Stable Habitats: Truncatelloidean mentioning
confidence: 99%